If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 * 7 + x * 7) + 7x = 9 Multiply 6 * 7 (42 + x * 7) + 7x = 9 Reorder the terms for easier multiplication: (42 + 7x) + 7x = 9 Remove parenthesis around (42 + 7x) 42 + 7x + 7x = 9 Combine like terms: 7x + 7x = 14x 42 + 14x = 9 Solving 42 + 14x = 9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 14x = 9 + -42 Combine like terms: 42 + -42 = 0 0 + 14x = 9 + -42 14x = 9 + -42 Combine like terms: 9 + -42 = -33 14x = -33 Divide each side by '14'. x = -2.357142857 Simplifying x = -2.357142857
| 12+2x=x | | X^6-2x^2+1=0 | | 8/0.08 | | (81x^6)^(1/2) | | 3t(8)+(-2)(7c)= | | -2y=-128 | | 5x+6=6+7x | | 7x+7=105-7x | | Y^2-10y+25=8 | | 3(x-0.5)+1=3x-0.5 | | 1+7x=3x+37 | | A(x)=-2x^2+300 | | 13t-3=11t+-9 | | 9y+7=7y+3+3y-7 | | 68=(1063)(149/360)r | | 2x+10-6x=-22 | | 3x+2y-2z=2 | | -2z^2+15=-21 | | 54+9h=225 | | 16.3k+19.2+7.5k=-63.1 | | 4x^6+x^3-6x^2-x^2+5= | | 31=2x+(2x-1) | | -6+6x-2x=14 | | (7r+5)(2r-6)=0 | | (4-5i)/(5-1) | | 2z+13=8z+1 | | 2x-1+x=-28 | | 9y+8=6y+1 | | X+4-3=6*5 | | 2-x+6x=37 | | 42=(960)(177/360)r | | 4x+5ys=12 |